1995
DOI: 10.1021/bi00037a036
|View full text |Cite
|
Sign up to set email alerts
|

An Acidic Motif within the Third Intracellular Loop of the .alpha.2C2 Adrenergic Receptor Is Required for Agonist-Promoted Phosphorylation and Desensitization

Abstract: The alpha 2C2 adrenergic receptor contains a highly acidic stretch of amino acids (EDEAEEEEEEEEEEEE) within the third intracellular loop. To investigate the role of this region, we utilized site-directed mutagenesis to delete these 16 amino acids as well as to substitute them with glutamine, thereby conserving size but not charge. The wild-type and mutated alpha 2C2 receptors were permanently expressed in CHO cells. Neither substitution nor deletion of this region affected receptor expression, agonist or antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 24 publications
(43 reference statements)
2
50
1
2
Order By: Relevance
“…In a study that used site-directed mutagenesis and transfected Chinese hamster ovary cells (CHO), mutant receptors with the glutamic acid repeat element either deleted or replaced with an equal number of charge-neutral glutamine recidues were found to be resistant to short-term, agonist-dependent, phosphorylationmediated desensitization. 21 In another study, mice with a disrupted a 2B -adrenoceptor gene failed to show the typical blood pressure increase after i.v. injection of subtype-nonselective a 2 -adrenoceptor agonists, whereas the centrally mediated hypotensive action of these agents was significantly accentuated.…”
Section: Discussionmentioning
confidence: 98%
“…In a study that used site-directed mutagenesis and transfected Chinese hamster ovary cells (CHO), mutant receptors with the glutamic acid repeat element either deleted or replaced with an equal number of charge-neutral glutamine recidues were found to be resistant to short-term, agonist-dependent, phosphorylationmediated desensitization. 21 In another study, mice with a disrupted a 2B -adrenoceptor gene failed to show the typical blood pressure increase after i.v. injection of subtype-nonselective a 2 -adrenoceptor agonists, whereas the centrally mediated hypotensive action of these agents was significantly accentuated.…”
Section: Discussionmentioning
confidence: 98%
“…The C-terminal third of the 3i loop of the ␣ 2A AR subtype is implicated in the interaction with ␤-arrestin, a protein that preferentially associates with G protein-coupled receptor kinase-phosphorylated receptors sustaining agonist-elicited homologous desensitization (23). For the ␣ 2 AR subtypes, G protein-coupled receptor kinase phosphorylation sites are in the N-terminal region of the ␣ 2A AR 3i loop (24,25), widely distributed throughout the ␣ 2B AR 3i loop, and presumed to be absent in the ␣ 2C AR 3i loop (13,26).…”
mentioning
confidence: 99%
“…Studies with peptide substrates and purified GRKs have suggested that acidic amino acids act to direct GRKmediated phosphorylation of specific Ser/Thr in GPCRs (16). Studies with the ␣ 2 C2 adrenergic receptor demonstrated that acidic amino acids are important in the agonist-dependent phosphorylation of this receptor (40). Removal of the large cluster of acidic residues in this receptor decreased the extent of phosphorylation of this receptor approximately 50% (40).…”
Section: Resultsmentioning
confidence: 99%
“…Studies with the ␣ 2 C2 adrenergic receptor demonstrated that acidic amino acids are important in the agonist-dependent phosphorylation of this receptor (40). Removal of the large cluster of acidic residues in this receptor decreased the extent of phosphorylation of this receptor approximately 50% (40). However, little is known about the role of acidic amino acids in directing phosphorylation of specific sites in other GPCRs in a cellular context.…”
Section: Resultsmentioning
confidence: 99%